Understanding Hotel Employees’ Perceptions of Guests with Disabilities in Ho Chi Minh City, Vietnam - Nguyen, Van Hoang; Do, Thi Lan Phuong (Centre For Tourism Planning and Development, 2024)
While previous research has mainly concentrated on understanding the requirements of guests with disabilities, there is a notable gap in exploring the perspectives held by hotel employees. This study endeavors to address this research gap by investigating how hotel employees in Ho Chi Minh City (HCMC) perceive guests with disabilities. Employing a mixed-methods approach, this research seeks to uncover employee attitudes and knowledge, their roles in fostering inclusivity, and the significance of communication between management and staff in elevating service quality. Notably, the study’s key findings underscore a significant link between employee contentment and customer satisfaction within hotels in HCMC, underscoring the pivotal role of effective communication in enhancing service quality. The research’s most prominent discovery indicates that a substantial proportion of hotel staff (88.5%) strongly agree on the importance of providing accessibility for guests with disabilities, as evident from the outcomes of the online survey. This outcome demonstrates a commendable high level of awareness among hotel employees concerning the specific needs of customers with disabilities. In terms of hotels’ overarching outlook towards guests with disabilities, a majority of managers voiced the perspective that hotels do not actively focus on disabled guests as a distinct market segment. These findings provide invaluable insights that can guide hotel managers and employees, contributing to a more comprehensive comprehension of how to establish an inclusive environment within the hospitality industry.